The viral effects of foreign trade and supply networks in the euro area - Virginia Di Nino; Bruno Veltri (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2020)
Containment measures of COVID-19 have generated a chain of supply and demand shocks around the globe with heterogeneous fallout across industries and countries. We quantify their transmission via foreign trade with a focus on the euro area where deep firms integration within regional supply chains and strong demand linkages act as a magnification mechanism. We estimate that spillover effects in the euro area from suppression measures in one of the five main euro area countries range between 15-28% the size of the original shock; negative foreign demand shocks depress euro area aggregate activity by about a fifth the size of the external shock and a fourth of the total effect is due to indirect propagation through euro area supply chain. Last, reopening to regional tourism softened the contraction of aggregate activity due to travel and tourism bans by about a third in the euro area. Our findings suggest that enhanced coordination of recovery plans would magnify their beneficial effects.
urn:nbn:de:gbv:3:2-129041
Keywords: F14; F23; F40; 330; COVID-19; supply networks; GVCs; euro area foreign trade